Interview with Mehmet Ali Birand. RAPPROCHEMENT BETWEEN GREECE AND TURKEY IS IRREVOCABLE: This interview was conducted by Jean Catsiapis - Birand, Mehmet Ali; Catsiapis, Jean (Études helléniques / Hellenic Studies, 2000)
--